Modeling social‐ecological problems in coastal ecosystems: A case study. Issue 6 (20th March 2014) - Forrester, John; Greaves, Richard; Noble, Howard; Taylor, Richard; Gilbert, Nigel; Bullock, Seth
<x xml:space="preserve">Abstract</x> Complex social‐ecological systems (SES) are not amenable to simple mathematical modeling. However, to address critical issues in SES (e.g., understanding ecological resilience/amelioration of poverty) it is necessary to describe such systems in their entirety. Based on empirical knowledge of local stakeholders and experts, we mapped their conceptions of one SES. Modelers codified what actors told us into two models: a local‐level model and an overarching multiple‐entity description of the system. Looking at these two representations together helps us understand links between the locally specific and other levels of decision taking and vice‐versa. This "bimodeling" approach is investigated in one SES in coastal Kenya. © 2014 Wiley Periodicals, Inc. Complexity 19: 73–82, 2014